Post-Fire Mechanical Properties Of Natural And Synthetic Fibre Composites - Nazri, Engku Afif Akramin Engku Muhammad (Universiti Sains Malaysia, 2021)
Sustainability is an important aspect in engineering design. Manufacturers are looking to find more sustainable materials as an alternative to synthetic fibres in composite. Natural fibres seem to be a great alternative to replace synthetic fibres in composite materials applications. However, the mechanical properties of the composite materials after exposure to fire needs to be considered in the design process. This study fills the research gap whereby the post-fire mechanical properties of natural fibre reinforced polyester and glass fibre reinforced polyester can be compared and analysed. In this study, jute fibre reinforced polyester and glass fibre reinforced polyester are fabricated by using wet hand layup method. Then, the physical appearance of the two composites after exposing it to fire for a certain duration are investigated and lastly the mechanical properties of room temperature and post-fire composites are compared by running a tensile test. The result of the study shows that in general, when exposed to fire for a short duration only, the composite retains most of its tensile properties with slight burn on the surface. But after exposing it to fire for a longer period, the resin is completely burnt, and the fibre is exposed to fire. This further decreases the mechanical properties of the composites. From the study, it can be stated E-glass fibre has better fire performance than jute fibre polyester composite.